'Hopeful adaptation' in health geographies: Seeking health and wellbeing in times of adversity. (June 2019) - Power, Andrew; Bell, Sarah L.; Kyle, Richard G.; Andrews, Gavin J.
Abstract: Living with adversity can create wide-ranging challenges for people's health and wellbeing. This adversity may arise through personal embodied difference (e.g. acquiring a brain injury or losing mobility in older age) as well as wider structural relations that shape a person's capacity to adapt. A number of dichotomies have dominated our understanding of how people engage with health and wellbeing practices in their lives, from classifying behaviours as harmful/health-enabling, to understanding the self as being defined before/after illness. This paper critically interrogates a number of these dichotomies and proposes the concept of 'hopeful adaptation' to understand the myriad, often non-linear ways that people seek and find health and wellbeing in spite of adversity. We highlight the transformative potential in these adaptive practices, rather than solely focusing on how people persist and absorb adversity. The paper outlines an agenda for a health geography of hopeful adaptation, introducing a collection of papers that examine varied forms of adaptation in people's everyday struggles to find health and wellbeing whilst living with and challenging adversity. Highlights: This paper looks at how people adapt to personal and structural challenges. People adapt to find health and wellbeing and to transform the challenges. The paper proposes the idea of 'hopeful adaptation' to understand these practices. It outlines an agenda for a health geography of adapting to adversity. It introduces a special issue on this subject.